2017
DOI: 10.1016/j.neuron.2017.09.032
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis Suggests Different Neural Correlates for Implicit and Explicit Learning

Abstract: SUMMARY A meta-analysis of non-human primates performing three different tasks (Object-Match, Category-Match, and Category-Saccade associations) revealed signatures of explicit and implicit learning. Performance improved equally following correct and error trials in the Match (explicit) tasks but it improved more after correct trials in the Saccade (implicit) task, a signature of explicit vs implicit learning. Likewise, error-related negativity, a marker for error processing, was greater in the Match (explicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 76 publications
2
26
1
1
Order By: Relevance
“…In our study, we found significant PC following saccades, regardless of stimulus conditions and tasks. This effect occurred within frequency bands previously associated with explicit learning and relevant stimuli processing (i.e., delta/theta and alpha/beta; Brincat & Miller, 2015;Loonis et al, 2017) and despite minimal changes in visual stimulation.…”
Section: Correlation Between Lfps and Saccade Parametersmentioning
confidence: 69%
See 2 more Smart Citations
“…In our study, we found significant PC following saccades, regardless of stimulus conditions and tasks. This effect occurred within frequency bands previously associated with explicit learning and relevant stimuli processing (i.e., delta/theta and alpha/beta; Brincat & Miller, 2015;Loonis et al, 2017) and despite minimal changes in visual stimulation.…”
Section: Correlation Between Lfps and Saccade Parametersmentioning
confidence: 69%
“…Interestingly, during contextual exploration hippocampal phase preceded PFC phase, while this relationship was reversed during target sampling. Similarly, Brincat and Miller (2015), as well as Loonis et al (2017), measured a strong hippocampus led phase coherence between 9 and 16 Hz following correct trial outcome feedback in macaque monkeys. Although some results must be interpreted cautiously due to the lack of homology between rodent and primate PFC (Carlén, 2017;Kaas, 2013), they reveal a degree of generalization across mammalian brains.…”
Section: Frequency-specific Pc By Visual Transient and Saccadesmentioning
confidence: 80%
See 1 more Smart Citation
“…A linear relationship between association strength and human fMRI was further observed in the MTL, frontal, temporal and parietal regions (Law et al, 2005), while beta oscillations in the monkey entorhinal cortex were shown to increase in a similar linear fashion as memories became stronger (Hargreaves et al, 2012). Outside the MTL, prefrontal oscillations in beta (Brincat & Miller, 2016) and theta frequencies (Loonis, Brincat, Antzoulatos, & Miller, 2017;Paz, Bauer, & Paré, 2008) also increase as memories are established. Together, the extant evidence suggests that a distributed network of regions tracks conditional associative learning, and recordings from nonhuman primates further indicates that theta and beta oscillations might provide a key signature of memory formation.…”
Section: Introductionmentioning
confidence: 74%
“…How can these two views be reconciled? In reward-based motor learning tasks, it is generally agreed that participants begin to reflect upon task structure and develop strategies upon encountering negative outcomes (Leow et al, 2016; Loonis et al, 2017; Manley et al, 2014; Maxwell et al, 2001), which occurs nearly immediately in the Preserve task after the introduction of binary feedback, due to a lack of generalisation of cerebellar memory (Codol et al, 2018). In contrast, in the Acquire task, participants experience an early learning phase with mainly rewarding outcomes, possibly suppressing development of explicit control and allowing for this early window of implicit reward-based learning.…”
Section: Discussionmentioning
confidence: 99%